2016
DOI: 10.21315/mjms2016.23.5.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preventive, Therapeutic and Protective Exercises on Hippocampal memory Mediators in Stressed Rats

Abstract: Methods: Fortymaleratswererandomlydividedintofourgroups:thecontrolgroupand thepreventive,therapeutic,andprotectiveexercisegroups.Thetreadmillrunningwasappliedat aspeedof20-21m/minandachronicstressof6hours/dayfor21days.Subsequently,thevariables weremeasuredinthehippocampus.Results: The findings revealed that the hippocampal CORT levels in the preventive exercise group had a significant enhancement compared to the control group. In the protective and particularly the therapeutic exercise groups, the hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Many other and our previous studies demonstrated that exercise leads to improvements in the memory and DS time in normal and emotional stress conditions by changing some brain mediators. [ 10 11 13 27 28 ] Although some studies demonstrated beneficial effects of exercise on memory,[ 29 30 ] some researchers reported that forced exercise significantly impaired memory. [ 5 31 ] In this regard, our previous study demonstrated that synchronized exercise with emotional stress did not significantly improve short-, mid-, and long-term memory deficits in restraint-stressed rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other and our previous studies demonstrated that exercise leads to improvements in the memory and DS time in normal and emotional stress conditions by changing some brain mediators. [ 10 11 13 27 28 ] Although some studies demonstrated beneficial effects of exercise on memory,[ 29 30 ] some researchers reported that forced exercise significantly impaired memory. [ 5 31 ] In this regard, our previous study demonstrated that synchronized exercise with emotional stress did not significantly improve short-, mid-, and long-term memory deficits in restraint-stressed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, exercise timing has shown various effects on memory in normal and restraint stress conditions in rodents. [ 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] The restraint stress was induced throughout the experimental period from 8:00 am to 14:00 pm each day. [ 21 23 ]…”
Section: Methodsmentioning
confidence: 99%
“…Exercise, is a well-known strategy to increase BDNF brain levels, so it has been proposed as a non-invasive way to mimic the effects of direct BDNF administration over chronic stress. Radahmadi et al (2016) found that the hippocampal BDNF increases in response to exercise after a chronic stress protocol. On the other hand, Dief et al (2015) showed that animals that followed a 30 days swimming training program improved their performance in the T maze after being exposed to chronic stress and this enhancement correlated with upregulation of hippocampal BDNF.…”
Section: The Effect Of Chronic Stress On Bdnf and The Link To Psychiamentioning
confidence: 99%
“…Radahmadi et al (2016) tested the effect of exercise during the exposure to stressors (“protective exercise”). Unlike preventive and therapeutic exercise, no increment on BDNF hippocampal levels was found.…”
Section: The Effect Of Chronic Stress On Bdnf and The Link To Psychiamentioning
confidence: 99%